Firm‐specific human capital investments as a signal of general value: Revisiting assumptions about human capital and how it is managed - Morris, Shad S.; Alvarez, Sharon A.; Barney, Jay B.; Molloy, Janice C. (Strategic Management Journal, 2017)
Research summary : Prior scholarship has assumed that firm‐specific and general human capital can be analyzed separately. This article argues that, in some settings, this is not the case because prior firm‐specific human capital investments can be a market signal of an individual's willingness and ability to make such investments in the future. As such, the willingness and ability to make firm‐specific investments is a type of general human capital that links firm‐specific and general human capital in important ways. The article develops theory about these investments, market signals, and value appropriation. Then, the article examines implications for human resource management and several important questions in the field of strategic management, including theories of the firm and microfoundations of competitive advantage . Managerial summary : While managers don't often use the terms firm‐specific and general skills, they certainly recognize that investments employees make in their skill sets are more or less relevant to a specific firm. For instance, investing in specific relationships within a firm or learning a firm's proprietary software would be considered firm‐specific investments. While such skills may seem relevant only to the particular firm in which they were invested, these investments may also send valuable signals to competing firms that such employees are willing and able to make similar investments elsewhere. Hence, managers should be interested in determining if a potential hire has made prior firm‐specific investments to help them know whether that person might be likely to make such investments in his or her future place of employment . Copyright © 2016 John Wiley & Sons, Ltd.